Prediction of Europium Retention in Perovskite: Potential Candidates for an Engineering Barrier in the Disposal of Radioactive Waste - Huemantzin B. Ortiz-Oliveros; Rosa Ma. Flores Espinosa; Pedro Ávila-Pérez; Daniel Cruz-Gonzalez; Noureddine Ouerfelli (Journal of Chemistry)
Perovskites, such as tausonite, are crystalline metal oxides with excellent optical and photocatalytic properties and have also been used successfully in the retention of metals, simulating the isotopes of uranium and plutonium. In this work, different pseudo-order and thermodynamic models were studied to achieve the prediction of the sorption of Eu3+ (chemical analogous for actinides) in tausonite. The effects of gamma irradiation and temperature on the structural characteristics of the material were determined, as an additional step in the evaluation of material as an engineering barrier in the disposal of radioactive waste. The results obtained show that the tausonite is resistant to the gamma irradiation and thermal energy. Likewise, it was possible to determine that europium sorption occurs through an exothermic and spontaneous reaction, as well as through the formation of surface complexes, where Eu3+ ions bind to sites on the tausonite by dipole-dipole interaction. Furthermore, it was shown that the sorption mechanism is influenced by diffusive phenomena, which participate in the formation of surface complexes. Additionally, a new sorption model with respect to pH was proposed, which allowed determining the physical parameter π. The evidence obtained suggests that π is a physical parameter that relates pH to an optimal value and could explain the equilibrium between the surface complexes that tausonite forms with europium. Likewise, the evidence suggests that 50 kg of tausonite would have the capacity to retain at least 26.59 g of alpha-emitting radionuclides, equivalent to a waste package (900 kg) with a maximum activity of 4000 Bq/g.